2018
DOI: 10.1108/ijoa-03-2018-1376
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to workplace innovation and career satisfaction in the public service

Abstract: Purpose The purpose of this paper is to study the influence of two climates for innovation constructs, namely, leadership and organisational culture, on workplace innovation and career satisfaction. Design/methodology/approach This study used structural equation modelling to test the data from 3,125 engineering professionals in the Australian Public Service (APS). Findings The structural model indicated that leadership for innovation and ambidextrous culture for innovation influenced workplace innovation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 89 publications
3
49
0
2
Order By: Relevance
“…In other words, the relationship between transformational leadership and sustainability was mediated by bureaucratic culture. This finding is in line with previous studies that found the mediating effect of organisational culture (Al-Ali et al, 2017;Cegarra-Leiva et al, 2012;Hussain et al, 2016;Panuwatwanich et al, 2008;Pradhan et al, 2017;Sattayaraksa & Boon-itt, 2016;Shim, Jo, & Hoover, 2015;Wipulanusat Panuwatwanich, & Stewart, 2018;). This finding is rationalised by the influence of transformational leadership itself on sustainability which, as this study revealed, requires mediation of bureaucratic culture in the context of the listed property development companies in Malaysia.…”
Section: Discussionsupporting
confidence: 93%
“…In other words, the relationship between transformational leadership and sustainability was mediated by bureaucratic culture. This finding is in line with previous studies that found the mediating effect of organisational culture (Al-Ali et al, 2017;Cegarra-Leiva et al, 2012;Hussain et al, 2016;Panuwatwanich et al, 2008;Pradhan et al, 2017;Sattayaraksa & Boon-itt, 2016;Shim, Jo, & Hoover, 2015;Wipulanusat Panuwatwanich, & Stewart, 2018;). This finding is rationalised by the influence of transformational leadership itself on sustainability which, as this study revealed, requires mediation of bureaucratic culture in the context of the listed property development companies in Malaysia.…”
Section: Discussionsupporting
confidence: 93%
“…Incorrect assessment of their own capabilities and objective conditions of professional growth and rank advancement, setting career goals that do not take into account all the goals in life in general, "defensive approach in the development of their careers", are career limiting factors [19]. At the same time, employee's personal qualities such as leadership, competence, high performance contribute to satisfaction with career and create career prerequisites [25].…”
Section: Methodsmentioning
confidence: 99%
“…Innovative leadership and win-win innovation culture influence workplace innovation. Organizations can also improve workplace innovation and career satisfaction by accrediting their engineers [4]. The results highlight the importance of providing opportunities for engineers to participate in creative and innovative projects so as to improve their careers.…”
Section: Introductionmentioning
confidence: 92%
“…However, due to the limitations of enterprise size and available resources, innovation in manufacturing or delivery processes is restricted by multiple factors [3]. Educators should support the development of engineers' innovative ability and adopt teaching methods, such as activities, courses, and curricula, to improve their innovative ability [4]. Innovative leadership and win-win innovation culture influence workplace innovation.…”
Section: Introductionmentioning
confidence: 99%